Pengembangan Sistem Informasi Geografis Masjid di Kelurahan Telanaipura, Kelurahan Legok dan Kelurahan Murni Berbasis Website - Apriani Yuyun Saputri; Try Susanti; Imam Arifa’illah Syaiful Huda (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Technology, especially Geographic Information System (GIS) technology, can make it easier and faster for users to check data through online mapping as a whole. GIS will display the places on the earth's surface, one of which is the location of the mosque. Due to the large number of mosques in Jambi Province and the lack of accurate and comprehensive mosque information, it is still difficult for the Indonesian Mosque Council (DMI) to find and supervise all mosque activities. Therefore, researchers created a Mosque Geographic Information System to help collect mosque data, search for mosque locations, and integrate mosque data. The system development method used is the SDLC method with the waterfall model, with the PHP programming language and MySQL database. The results obtained from the GIS website for this mosque are capable of displaying a geographic information system that displays mosque information, so that it can assist in searching for mosque information and data quickly and accurately.